Competition network structure and product market entry - Skilton, Paul F.; Bernardes, Ednilson (Strategic Management Journal, 2015)
This study proposes and tests a theory of the effects of competition network structure on product market entry. Competition networks are defined as the patterns of interdependence between rivals that emerge from direct competition. Studying networks based on competitive interdependence allows us to extend social network theory to new territory and to enhance our understanding of product market entry. We propose that the size, interconnectedness and diversity of competition networks influence subsequent product market entry in a systemic way. We test our hypotheses in a unique dataset drawn from the aircraft modification industry . Copyright © 2014 John Wiley & Sons, Ltd.